Stalking and age. - Sheridan, Lorraine; Scott, A.; North, A. (Educational Publishing Foundation, 2014)
Few data exist concerning older and younger stalkers. This study compares 3 age groups of stalker [aged 16 or under (n = 19), aged 17–59 (n = 1,499), aged 60 or over (n = 86)] on 83 variables pertaining to demographics, the stalking process, the impact of stalking, and victim and third party responses. Self-defined victims of stalking provided the data. Just 11 of the variables differed significantly by age group. All 3 age groups were equally violent. Older victims of stalking were doubly disadvantaged, however, in that they were most likely to be injured by their stalkers but least likely to be taken seriously. The nature of the stalking behaviors and the negative impact of stalking was equal across the 3 age groups. Motivations for stalking would appear to reflect the age-related contexts in which stalking takes place. Stalking and stalking victimization would appear to be partially but not wholly limited by age